Role of Cameral Tax Inspection in the Tax System - Turaev Alijon Akmal o’g’li (Research Parks Publishing LLC, 2022)
This article analyzes the importance of in-house inspections and their specific features in the correct calculation of mandatory payments to the state budget through the control of the activities of business entities on the basis of tax legislation.